The Purification Of Rennin-Like Protease From Lactobacillus Paracasei Isolated From Ettawa Goat Milk - Wendry Setiyadi Putranto; Apon Zaenal Mustopa; Arizah Kusumawati; Anika Prastyowati (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2020)
There is a protease produced by bateria that has characteristics similar to rennin from a calf. Rennin has the ability to clot casein in milk. Rennin-like protease (RLP) is produced by bacteria extracellularly. Lactic Acid Bacteria (LAB) have the potential to be developed for RLP production because they are safe and non-pathogenic bacteria. Rennin is needed in the process of milk coagulation to subsequently obtain a curd in the process of making cheese. In this study, the LAB isolated from Ettawa goat milk (isolate 2.12) which produced RLP was 99% identical to Lactobacillus paracasei based on 16S rRNA gene sequence analysis. The purification of the RLP L. paracasei 2.12 with 60% ammonium sulfate deposition, dialysis, and filtration gel chromatography Sephadex G-50 showed a single 38 kDa protein band with SMCA/SPA was 4.48 higher than that of the calf rennet with a ratio value of 1, therefore in this study, RLP L. paracasei 2.12 was developed as an alternative to renin in cheese making.